Phytoconstituents and therapeutic potential of Nyctanthes arbortristis Linn. - Sasmal, D.; Das, Sanjita; Basu, S. P. (Pharmacognosy Reviews)
Nyctanthes arbortristis Linn. is one of the well known medicinal plant. It is a common wild hardy large shrub or small tree. It is a native of India, distributed wild in sub-Himalayan regions and southwards to Godavari. Different parts of this plant are used in Indian systems of medicine for various pharmacological actions. The rural people of Orissa use Nyctanthes arbortristis L. to cure various ailments. It’s claimed traditional uses have been proved on scientific basis using in-vitro and in-vivo experiments. The present study will give comprehensive information on the chemical constituents and mainly pharmacological activities of this plant.
Keywords: Nyctanthes arbortristis L.; Pharmacology; Phytochemistry; Review